ELABORATION AND CHARACTERIZATION OF NANOCRYSTALLINE CADMIUM OXIDE FILMS - H., Benattou; N., . Benaramdane, . Bouzidi* A. (university of eloued جامعة الوادي, 2020)
Cadmium oxide in thin film was deposited on glass substrates by spray pyrolysis technique from aqueous solution of cadmium nitrate. The diagrams of X-ray diffraction show that the films are polycrystalline. Morphological study shows uniform deposited film and submicron sized grains growth perpendicularly on substrate surface. Optical gap energy of cadmium oxide was estimated to be 2.15eV. Optical study shows that CdO film transmitted in visible and in the near red infrared wavelength range. The conductivity study indicates a semiconducting behavior of cadmium oxide in thin films. Dielectric response of cadmium oxide films was interpreted by orientation and space charge polarization.
artical
Keywords: CdO thin films; Spray pyrolysis; Morphological properties; AC conductivity; Dielectric properties.